2019
DOI: 10.29252/nbr.6.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Induced genetic and morphological changes in Catharanthus roseus L. by cold atmospheric plasma

Abstract: Catharanthus roseus is widely cultivated around the world. Cold atmosphere plasma (CAP) has been used to improve crop plants seed germination, and plant growth. In the present study, three different times of CAP (40, 50 and 60s) were used for the treatment of C. roseus seeds, and the changes in morphological traits, antioxidant enzymes and the genetic content of the treated plants were examined. Cold plasma (50s) markedly raised the seed germination, length of the leaves and the stem length of the plants in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A similar observation was made in wheat using DBD air plasma treatment [ 43 ]. Helium-plasma treatment of Catharanthus roseus seeds also resulted in catalase and peroxidase activities increase [ 66 ]. Švubová et al [ 49 ] observed an increase in SOD activity in pea seedlings for all three working gases (air, O 2 , N 2 ) using Diffuse Coplanar Surface Barrier Discharge (DCSBD; volume power density 80 W/cm 3 ), except for the treatment times that completely inhibited the germination (180 and 300 s in N 2 -generated NTP).…”
Section: Interaction Of Non-thermal Plasma With Biological Materiamentioning
confidence: 99%
“…A similar observation was made in wheat using DBD air plasma treatment [ 43 ]. Helium-plasma treatment of Catharanthus roseus seeds also resulted in catalase and peroxidase activities increase [ 66 ]. Švubová et al [ 49 ] observed an increase in SOD activity in pea seedlings for all three working gases (air, O 2 , N 2 ) using Diffuse Coplanar Surface Barrier Discharge (DCSBD; volume power density 80 W/cm 3 ), except for the treatment times that completely inhibited the germination (180 and 300 s in N 2 -generated NTP).…”
Section: Interaction Of Non-thermal Plasma With Biological Materiamentioning
confidence: 99%